As relações entre os conceitos de natureza e feminino na Dialética do Esclarecimento - Efraim, Raquel (2011)
The utmost purpose of this dissertation is the full understanding of the hypothesis presented by Adorno and Horkheimer in their book Dialectic of Enlightenment, which approaches the relationship between the concepts of nature and the women s world, and seek to make evidence, through weaving an activity common to all the females portrayed in the Odyssey, the work analyzed by these authors, followers of the School of Frankfurt theories of a second viable means to highlight the relevant role of women in the Antiquity. So as to attain such objective, two main paths have been followed: the first one aimed at studying the theory brought about by Adorno and Horkheimer while, simultaneously going deeper into the interpretation such authors have made of Homer s epopee. When describing the Dialectic of Enlightenment, the authors had, as their prime purpose, the investigation of the bond between reason and domination and used The Odyssey to set the grounds for their theory; nevertheless, due to the allegoric means they based their work upon, they ended up by inserting domination into the roots of rational thought. Ulysses, under their viewpoint, was the model of a bourgeois man who should govern Nature and himself on behalf of self-preservation. Adorno and Horkheimer introduced such a strict theory that finds parallel only in the conceptual strictness they criticized. In the narrow bond they created between reason and domination, the women represented in the Dialectic of Enlightenment by two essential figures, the wife and the prostitute, do not manage to find any other way of behavior, besides being in full compliance with the rules of their time. The second path intruded into the weaving and construed it as a way-out for the scheme proposed by Adorno and Horkheimer. By virtue of this (cultural) activity, described as a female talent, a quite different approach from the one that bound nature and women s role could be found. Therefore, weaving, which contains in itself an etymological bond with the word "text", stands out as a possibility of the feminine way of speaking, an amplification of women's voice in the Antiquity, besides being their means of participation in the outside world, a world that is so different from the home environment to which they usually belong